Nucleosome repositioning during differentiation of a human myeloid leukemia cell line - Teif, Vladimir; Mallm, Jan-Philipp; Rippe, Karsten; Eils, Roland; Langowski, Jörg (Nucleus, 2017)
Cell differentiation is associated with changes in chromatin organization and gene expression. In this study, we examine chromatin structure following differentiation of the human myeloid leukemia cell line (HL-60/S4) into granulocytes with retinoic acid (RA) or into macrophage with phorbol ester (TPA). We performed ChIP-seq of histone H3 and its modifications, analyzing changes in nucleosome occupancy, nucleosome repeat length, eu-/heterochromatin redistribution and properties of epichromatin (surface chromatin adjacent to the nuclear envelope). Nucleosome positions changed genome-wide, exhibiting a specific class of alterations involving nucleosome loss in extended (∼1kb) regions, pronounced in enhancers and promoters. Genes that lost nucleosomes at their promoters showed a tendency to be upregulated. On the other hand, nucleosome gain did not show simple effects on transcript levels. The average genome-wide nucleosome repeat length (NRL) did not change significantly with differentiation. However, we detected an approximate 10 bp NRL decrease around the haematopoietic transcription factor (TF) PU.1 and the architectural protein CTCF, suggesting an effect on NRL proximal to TF binding sites. Nucleosome occupancy changed in regions associated with active promoters in differentiated cells, compared with untreated HL-60/S4 cells. Epichromatin regions revealed an increased GC content and high nucleosome density compared with surrounding chromatin. Epichromatin showed depletion of major histone modifications and revealed enrichment with PML body-associated genes. In general, chromatin changes during HL-60/S4 differentiation appeared to be more localized to regulatory regions, compared with genome-wide changes among diverse cell types studied elsewhere.
Gesehen am 23.10.2018